2008
DOI: 10.1590/s1516-31802008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian version of the Body Dysmorphic Disorder Examination

Abstract: CONTEXT AND OBJECTIVE:Body image improvement is considered to be the main reason for undergoing plastic surgery. The objective was to translate the body dysmorphic disorder examination (BDDE) into Brazilian Portuguese and to adapt and validate this questionnaire for use in Brazil. DESIGN AND SETTING:Cross-sectional survey, at the Department of Plastic Surgery of Universidade Federal de São Paulo. METHODS:The BDDE was fi rst translated into Portuguese and then back-translated into English. These translations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
1
12
0
12
Order By: Relevance
“…In the same study by MacSween et al [11], women with RA achieved better scores than obese women with regard to the body domain. Likewise, in a study involving women who desired cosmetic surgery, Jorge et al [13] found a worse body image score in the experimental group. These findings suggest that women with RA have an intermediate perception of body image that falls between that of healthy women from the community and those with complaints related to esthetic issues.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the same study by MacSween et al [11], women with RA achieved better scores than obese women with regard to the body domain. Likewise, in a study involving women who desired cosmetic surgery, Jorge et al [13] found a worse body image score in the experimental group. These findings suggest that women with RA have an intermediate perception of body image that falls between that of healthy women from the community and those with complaints related to esthetic issues.…”
Section: Discussionmentioning
confidence: 91%
“…The score ranges from 0 to 168, with higher scores denoting a worse perception of body image [13]. • The Rosenberg Self-Esteem Scale: a self-esteem assessment measure validated for the Portuguese language that contains ten questions designed to globally assess an individual's positive or negative attitude regarding himself/herself.…”
Section: Evaluation Instrumentsmentioning
confidence: 99%
“…All data evaluated here were retrieved by administering the Brazilian version of the Body Dysmorphic Disorder Examination. 26 The Body Dysmorphic Disorder Examination and the clinical assessment for body Plastic and Reconstructive Surgery • February 2016 dysmorphic disorder 3 were used to classify the participants into those with and without body dysmorphic disorder symptoms. Sociodemographic (e.g., name, sex, age, and ethnicity) and clinical characteristics (e.g., history of previous cosmetic procedures, psychological/psychiatric treatment, and sexual abuse) of the study population were also obtained through a clinical interview.…”
Section: Methodsmentioning
confidence: 99%
“…33 Studies have reported retesting as early as a few hours after baseline testing. [24][25][26][27][28] The longer the time that elapses is, the lower the measured reliability will be, and the more likely it will be that knowledge or attitudes have in fact changed. 40 The instrument was tested for test-retest reliability (reproducibility) in three interviews conducted by two independent interviewers.…”
Section: Reliabilitymentioning
confidence: 99%
“…The number of patients participating in the cultural adaptation, reliability and validity phases was similar to that used in previous studies evaluating the psychometric properties of social construct measurements in plastic surgery populations, [23][24][25][26][27][28][29] and was in accordance with the methodology internationally accepted and used for translation, cultural adaptation and validation of instruments. [30][31][32][33][34] According to Sapnas and Zeller, 34 the traditional protocol for determination of an adequate sample size based on power analysis is not appropriate for studies assessing the psychometric properties of social construct measurements; a total sample size of 50 subjects or more is adequate for representing the study population.…”
Section: Introductionmentioning
confidence: 99%